2018
DOI: 10.1039/c8ra07396a
|View full text |Cite
|
Sign up to set email alerts
|

Designed formation of Co3O4@NiCo2O4 sheets-in-cage nanostructure as high-performance anode material for lithium-ion batteries

Abstract: Unique Co3O4@NiCo2O4 sheets-in-cage hybrid nanoparticles are successfully fabricated through a template-assisted method. When evaluated as an anode material, they exhibit highly enhanced electro-chemical properties for lithium storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…The great surface area and the suitable size of pores cause to create the accessibility and high frequency of uniform spaces, which can improve the drug carrier's efficiency. Compared to the cases reported in previous studies, which show a decrease in the active surface after the formation of LDH on ZIF, in this work, due to the simultaneous formation and growth of LDH crystals with the conversion of ZIF crystal form, the active surface was very significant [54,55].…”
Section: The Results Of Rt-pcr and Western Blot Analysiscontrasting
confidence: 79%
“…The great surface area and the suitable size of pores cause to create the accessibility and high frequency of uniform spaces, which can improve the drug carrier's efficiency. Compared to the cases reported in previous studies, which show a decrease in the active surface after the formation of LDH on ZIF, in this work, due to the simultaneous formation and growth of LDH crystals with the conversion of ZIF crystal form, the active surface was very significant [54,55].…”
Section: The Results Of Rt-pcr and Western Blot Analysiscontrasting
confidence: 79%
“…Apart from the synergistic effects between the NiCo 2 O 4 and Co 3 O 4 , it is also believed that the extra phase of Co 3 O 4 imparts in the electrochemical reactions and exhibits high capacity due to the storage of 8 Li + ions per formula unit (Co 3 O 4 +8Li + +8e − →3Co+4Li 2 O). In addition, a comparative study of the electrochemical performances of the current work and the previously reported literature of NiCo 2 O 4 electrode materials based on different morphologies has been summarized in Table 2 [13,20,29,42–48] . It can be concluded that the nanowire morphology of NiCo 2 O 4 /Co 3 O 4 electrode exhibits high reversible capacity and superior cycling stability than others.…”
Section: Resultsmentioning
confidence: 72%
“…(1)] and the solid electrolyte interphase (SEI) that resulted from electrolyte decomposition [26,27] . In contrast, the two anodic peaks can be also seen for both the electrodes at ∼1.4 V and ∼2.1 V, which could be assigned to the oxidation of Ni and Co metals to Ni 2+ and Co 3+/2+ , respectively [28,29] . During the second cathodic scan, the reduction peak obtained at ∼0.8 V shifted to the higher potential of ∼1.1 V, due to the improved reaction kinetics after the first lithiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations